Task Forces on Housing and Urban Development, II. Financing of Urban Development - Planning Commission (Planning Commission, 1985)
Municipal government in India covers five distinct types of urban local authorities; the municipal corporations, the municipal councils, the notified area committees, the town area committees and the cantonment boards. The municipal corporations and councils are fully representative bodies, while the notified area and town area committees are either fully or partially nominated bodies. The cantonment boards are created under a capital legislation and consist of partially elected authorities supervised by the Union Ministry of Defence. The municipal authorities are creatures of the state governments where the district, officer exercises indirect control over their functioning, except in the case of the municipal corporations which deal directly with the state government. Unlike the rural local authorities (Panchayati raj), the urban local authorities are not organized hierarchically, nor are their activities integrated with either the rural local authorities or the states field administration in the districts.
Financing of Urban Development
Government of India